2021
DOI: 10.1002/pon.5736
|View full text |Cite
|
Sign up to set email alerts
|

Family rules, routines, and caregiver distress during the first year of pediatric cancer treatment

Abstract: Objective A new diagnosis of pediatric cancer may disrupt family functioning. The current study aimed to describe changes in family rules and routines during the first year of pediatric cancer treatment, and to explore associations with demographics, illness factors, and caregiver distress. Methods This exploratory mixed‐methods, cross‐sectional study examined 44 primary caregivers of youth in treatment for a new cancer diagnosis in 2019 and 2020, before the onset of the COVID‐19 pandemic. Caregivers completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 31 publications
0
16
1
2
Order By: Relevance
“…Families in the present study adapted to COVID-19 and cancer through systems of organization and communication. Previous work emphasizes the importance of consistent family rules and routines during times of stress, including after a cancer diagnosis [28] and during the COVID-19 pandemic [3]. However, families in the present study reported many cancer and COVID-related disruptions to rules and routines.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Families in the present study adapted to COVID-19 and cancer through systems of organization and communication. Previous work emphasizes the importance of consistent family rules and routines during times of stress, including after a cancer diagnosis [28] and during the COVID-19 pandemic [3]. However, families in the present study reported many cancer and COVID-related disruptions to rules and routines.…”
Section: Discussioncontrasting
confidence: 78%
“…This study is part of a larger study that began prior to the COVID-19 pandemic that sought to examine changes in the family home environment following a new diagnosis of pediatric cancer [28]. A subset of study data was collected during the COVID-19 pandemic, and these data were examined separately from the larger dataset given the impact of the COVID-19 pandemic on the family home environment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of studies conducted in various research centers with the application of various research tools indicate a high level of negative emotions as well as toxic stress among parents of children suffering from cancer [ 12 , 24 , 25 , 26 , 27 , 28 ]. In addition, the results of the current study have shown that a significant percentage of parents struggle with psychoemotional problems, regardless of the duration of the child’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, mothers who become an important part of a therapeutic team are more vulnerable to emotional and physical overload as compared to fathers [ 5 ]. Although Pinquart [ 33 ] and Baters [ 28 ] indicated a higher level of perceived stress in women as compared to men, Rahmani et al [ 4 ] did not find any significant differences in the incidence of negative emotions depending on parents’ gender. On the other hand, the meta-analysis of van Warmerdam [ 34 ] and the study conducted by Mekonnen [ 5 ] may lead to a conclusion that there are also other factors which may be responsible for the onset of depression such as single parenthood or lack of support [ 5 ].…”
Section: Discussionmentioning
confidence: 99%